EFFECT OF METHODES , QUANTITIES AND INTERVALS OF IRRIGATION ON SOME GROWTH CHARACTERS OF Robinia pseudoacacia L . TRANSPLANTS AFTER PLANTING - Mudhafar O . Abdullah (Mesopotamia Journal of Agriculture)
The experiment was conducted in Mosul University Compus which is located on eastside of Tigris River . The study was applced during the period form the beginning of March until November, 2006 in order to investigate the effects of irrigation methods (bar soil surface, covering soil surface by gravels and fitting perpendicular plastic pipes), irrigation quantities (4, 6 and 8 liters) and Irrigation intervals (2, 3 and 4 days) on growth characters of Robinia pseudoacacia L . The factorial experiment was conducted according to Randomized Complete Block Design and used Duncan method to comper the treatments means. At the end of experiment the following characters were tested, survival percentage, diameter growth increment, height Growth increment and branches number increment. and the most importment results were as follows: 1) The fitting of perpendicular plastic pipe , quantity of irrigation (8) litters and the shorter irrigation interral gave the best results in case of all studied characters . 2) The following interaction (perpendicular plastic pipe and 8 liters), (perpendicular plastic pipe and each 2 days irrigation) and (8 liters and 2 days irrigation) gave the best results in the case of all studied characters as comper with the other interactions . 3) Due to the tripple interaction among the studied factors; the interaction of (perpendicular plastic pipe and 8 liters and 2 days) gave the best results of all studied characters as comper with the other tripple interaction.